On Generalized bell numbers for complex argument - Corcino, Roberto B.,; Montero, Maribeth B.,; Corcino, Cristina B., (Utilitas Mathematica, 2012)
In this paper, the (r, β)-Stirling numbers and (r, β)-Bell numbers for complex arguments are defined using Hankel contour and an investigation which of the properties of the classical Stirling and Bell numbers survive, is done.